Positive electrode material and preparation method thereof, positive electrode plate and secondary battery

By forming a porous mesh carbon layer structure on the sodium vanadium fluorophosphate particles, the problem of insufficient electronic conductivity and ion diffusion rate of the NVPF cathode material is solved, and the performance and life of the secondary battery are significantly improved.

CN119742341APending Publication Date: 2025-04-01HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411930464.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

As the positive electrode material of sodium vanadium fluorine phosphate (NVPF), the sodium ion battery has a low electron conductivity and a slow ion diffusion rate, resulting in a low actual specific capacity of the secondary battery and an unsatisfactory rate performance.

Method used

By uniformly distributing sodium vanadium fluorophosphate particles in the carbon layer, a positive electrode material with a porous mesh structure is formed, thereby improving electron conductivity and sodium ion transport efficiency. This structure is formed by the tight combination of the porous mesh structure of the carbon layer and the sodium vanadium fluorophosphate particles, with suitable porosity and thickness.

Benefits of technology

It improves the charging efficiency, discharge efficiency and electrochemical performance of the secondary battery, extends the service life of the secondary battery, and improves its thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742341A_ABST
    Figure CN119742341A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electric device, and belongs to the technical field of battery positive electrode materials. The positive electrode material comprises a carbon layer and sodium vanadium fluorophosphate particles distributed in the carbon layer, wherein the carbon layer coats the sodium vanadium fluorophosphate particles; the carbon layer is in a porous net shape, and the thickness of the carbon layer is selected from 3 nm to 6 nm; and the porosity of the positive electrode material is 10%-35%. The preparation method comprises the following steps: obtaining gel slurry by adopting microwave-assisted hydrothermal treatment and a sol-gel technology, drying the gel slurry, and calcining to obtain the positive electrode material. According to the positive electrode material, the wettability of an electrolyte and the electron and sodium ion transmission efficiency are improved, and the charge-discharge efficiency and the electrochemical performance of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] As a potential alternative to lithium-ion batteries, sodium-ion batteries have attracted widespread attention in recent years due to their abundant resources, low cost, and environmental friendliness. In practical applications, sodium ions are larger in volume and mass than lithium ions, and are more difficult to embed and extract from electrode materials, which poses challenges to battery performance such as battery energy density, cycle stability, and rate performance.

[0003] In sodium-ion batteries, cathode materials are key components of electrochemical reactions, and their performance has a crucial impact on the overall performance of the battery. High-performance cathode materials can not only provide higher energy density, but also maintain good structural stability and cycle stability during charge-discharge processes.

[0004] Sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVPF) is an anionic compound, commonly used as a positive electrode material for sodium ion batteries. Its open framework structure provides a three-dimensional ion diffusion channel, which is conducive to the rapid deintercalation and diffusion of sodium ions, and has a high ion diffusion rate and voltage platform as well as good cycle stability. However, NVPF also has some disadvantages, mainly including low electronic conductivity and slow ion diffusion rate, which leads to low actual specific capacity and unsatisfactory rate performance when applied to secondary batteries, thus limiting its further application and development.

[0005] In order to further improve the electronic conductivity and sodium ion transmission efficiency of NVPF positive electrode materials and improve the actual efficiency and cycle life of the battery, the technical solution of the present application is specially proposed. Summary of the invention

[0006] In view of the technical problems existing in the background technology, the present application provides a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electrical device, aiming to save preparation costs, optimize the preparation process and further improve the actual efficiency and cycle life of the secondary battery.

[0007] In a first aspect, an embodiment of the present application provides a positive electrode material, including a carbon layer and sodium vanadium fluorophosphate particles distributed in the carbon layer, wherein the carbon layer covers the sodium vanadium fluorophosphate particles;

[0008] The carbon layer is in a porous network shape, and the thickness of the carbon layer is selected from 3nm to 6nm;

[0009] The porosity of the positive electrode material is 10% to 35%.

[0010] In the technical solution of the embodiment of the present application, the carbon layer of the positive electrode material is in a porous network, and the porous structure of the carbon layer of the positive electrode material uniformly covers the sodium vanadium fluorophosphate particles. The appropriate thickness and porosity of the porous network carbon layer have good thermal stability and provide a more efficient channel for the transmission of electrons, thereby improving the electronic conductivity of the positive electrode material, and being beneficial to the penetration of the electrolyte and the rapid transmission of sodium ions, thereby being beneficial to improving the electrochemical performance of the secondary battery in terms of charging efficiency and discharging efficiency, while improving the thermal stability of the secondary battery and extending the service life of the secondary battery.

[0011] In some embodiments, the cathode material has at least one of the following characteristics:

[0012] (1) The pore diameter is 2nm to 8nm;

[0013] (2) Specific surface area is 10m 2 / g~50m 2 / g;

[0014] (3) Powder resistivity ≤ 80000Ω·cm.

[0015] In this embodiment, the pore size of the positive electrode material, that is, the pore size of the porous network structure presented by the carbon layer of the positive electrode material, the appropriate pore size and specific surface area are beneficial to improving the conductivity of the positive electrode material and achieving good infiltration of the electrolyte without affecting the compaction density and structural stability of the positive electrode material; at the same time, the powder resistivity of the positive electrode material is within a suitable range, which is beneficial to the rate of electron transmission being within a suitable range, obtaining good electron conductivity, and being beneficial to the corresponding secondary battery having high rate performance, and good stability and safety.

[0016] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0017] mixing the reducing sugar and the alkaline solution to obtain a first dispersion;

[0018] The first dispersion is mixed with a cationic modifier and subjected to a first reaction treatment to obtain an adhesive;

[0019] The binder, a phosphorus source, a sodium source, a fluorine source, a vanadium source and a complexing agent are mixed to obtain a precursor solution;

[0020] The precursor solution is treated by microwave reaction to obtain a gel slurry;

[0021] The gel slurry is dried and then calcined to obtain the positive electrode material.

[0022] In the technical scheme of the embodiment of the present application, the obtained cation-modified adhesive, phosphorus source, sodium source and vanadium source, complexing agent, etc. are mixed and microwave-treated to form a tight composite structure, and calcined to obtain a positive electrode material with a suitable porous mesh carbon layer; in the positive electrode material, the porous carbon structure is compounded with NVPF in an in-situ co-doping manner, and the porous mesh carbon layer uniformly covers the sodium vanadium fluorophosphate particles to form a conductive network and is tightly combined with the sodium vanadium fluorophosphate particles, which not only ensures the continuity of ion transmission and improves the electronic conductivity of the positive electrode material, but also effectively alleviates the change in the volume of the positive electrode material during the charge-discharge process, and enhances the structural stability of the positive electrode material. The porous mesh of the carbon layer of the positive electrode material is also conducive to the penetration of the electrolyte and the rapid transmission of sodium ions, further improving the charging rate, discharge rate and electrochemical performance of the corresponding secondary battery.

[0023] In some embodiments, the step of mixing the reducing sugar and the alkaline solution to obtain a first dispersion comprises:

[0024] mixing the reducing sugar and the alkaline solution at a first mixing temperature for a first mixing time to obtain the first dispersion;

[0025] Wherein, the first mixing temperature is 40°C to 80°C, and the first mixing time is 0.5h to 3h; and / or,

[0026] The concentration of hydroxide ions in the alkaline solution is 0.1 mol / L to 0.5 mol / L.

[0027] In this embodiment, the reducing sugars are activated in the alkaline solution, the reaction efficiency is improved, and the ionization degree of the hydroxyl groups in the reducing sugars is appropriate, which fully reacts with the cationic modifier, which is conducive to obtaining a binder with a suitable degree of cationic modification.

[0028] In some embodiments, the first dispersion is mixed with a cationic modifier and subjected to a first reaction treatment to obtain an adhesive, comprising:

[0029] After the first dispersion liquid and the cationic modifier are mixed, reacting at a first reaction temperature for a first reaction time to obtain a first reaction liquid;

[0030] After the first reaction liquid is neutralized, it is purified to obtain the adhesive;

[0031] Wherein, the first reaction temperature is 30°C to 60°C, the first reaction time is 6h to 10h; and / or,

[0032] The molar ratio of the cationic modifier to the glucose unit in the first dispersion is (1-4):1.

[0033] In this embodiment, after mixing a suitable amount of the cationic modifier and the first dispersion, the reaction is carried out at a suitable temperature for a suitable time, which is conducive to the glucose unit in the first dispersion and the cationic modifier to fully react at a high rate, and avoids side reactions caused by excessively high temperatures, thereby facilitating the acquisition of a binder with uniform performance. The cationic modified binder improves the dispersibility and reactivity of the reducing sugars, provides good interfacial compatibility for its subsequent composite process, and helps to form a uniform positive electrode material.

[0034] In some embodiments, the step of neutralizing the first reaction solution comprises:

[0035] Adding a pH adjuster to the first reaction solution to a pH value of 6 to 7 to obtain a pre-treated solution;

[0036] Stirring the pretreatment solution at a pH value of 6 to 7 and a temperature of 50° C. to 90° C. for 6 to 10 hours; and / or,

[0037] The step of purifying the first reaction solution after neutralization treatment comprises:

[0038] The neutralized first reaction solution is dialyzed.

[0039] In this embodiment, the excess alkali in the first reaction solution is neutralized to prevent excessive degradation or excessive structural changes of reducing sugars, thereby ensuring that the degree of modification of reducing sugars meets expectations. After further purification, impurities other than the adhesive are removed to improve the purity of the adhesive.

[0040] In some embodiments, the step of treating the precursor solution with microwave reaction to obtain a gel slurry comprises:

[0041] subjecting the precursor solution to a first microwave power and a second reaction temperature for a second reaction time to obtain the gel slurry;

[0042] Wherein, the first microwave power is 200W-500W, the second reaction temperature is 120°C-160°C, and the second reaction time is 0.5h-2h.

[0043] In this embodiment, the precursor solution is subjected to microwave hydrothermal treatment, a porous network is initially formed, and the sodium vanadium fluorophosphate precursor is evenly distributed in the porous network, which is beneficial for the subsequent preparation of a positive electrode material with a specific structure.

[0044] In some embodiments, the gel slurry is dried and then calcined to obtain a positive electrode material, comprising:

[0045] drying the gel slurry at a first drying temperature for a first drying time to obtain a gel dry powder;

[0046] calcining the gel dry powder to obtain a positive electrode material;

[0047] Wherein, the first drying temperature is 100° C. to 120° C., and the first drying time is 6 h to 12 h; and / or,

[0048] The step of calcining the gel dry powder to obtain a positive electrode material comprises:

[0049] In a first protective gas, the gel dry powder is calcined at a first temperature and for a first insulation time to obtain a first calcined material;

[0050] In a second protective gas, the first calcined material is calcined at a second calcination temperature and for a second holding time to obtain a second calcined material;

[0051] The second calcined material is subjected to grinding and screening to obtain the positive electrode material;

[0052] Wherein, the first protective gas and the second protective gas are protective gases, the first calcination temperature is 350°C to 550°C, the first insulation time is 0.5h to 2h, the second calcination temperature is 700°C to 800°C, and the second insulation time is 1h to 3h;

[0053] The protective gas includes at least one of argon and nitrogen.

[0054] In this embodiment, after the gel slurry is dried and calcined under the above conditions, a positive electrode material having a porous mesh carbon layer and sodium vanadium fluorophosphate particles uniformly distributed in the carbon layer is obtained. The porous mesh carbon layer structure is uniformly coated with sodium vanadium fluorophosphate particles and has a suitable porosity. The carbon layer also has a suitable thickness, which provides a more efficient channel for the transmission of electrons, improves the electronic conductivity of the positive electrode material, and is also beneficial to the penetration of the electrolyte and the rapid transmission of sodium ions, further improving the charge and discharge efficiency and electrochemical performance of the corresponding secondary battery.

[0055] In some embodiments, the preparation method satisfies at least one of the following conditions:

[0056] (1) the molar ratio of the phosphorus element in the phosphorus source, the sodium element in the sodium source, the fluorine element in the fluorine source, and the vanadium element in the vanadium source is 2:3:3:2;

[0057] (2) The mass ratio of the binder, the vanadium source and the complexing agent is 1:1:(1-5);

[0058] (3) The cationic modifier includes at least one of 2,3-epoxypropyltrimethylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride and 2-diethylaminoethylammonium chloride;

[0059] (4) The phosphorus source is selected from phytic acid;

[0060] (5) The sodium source comprises at least one of sodium hydroxide, sodium fluoride, sodium carbonate and sodium bicarbonate;

[0061] (6) The fluorine source comprises at least one of ammonium fluoride, polytetrafluoroethylene and sodium fluoride;

[0062] (7) The vanadium source includes at least one of ammonium vanadate and ammonium metavanadate;

[0063] (8) The complexing agent includes at least one of citric acid, oxalic acid and tannic acid.

[0064] In this embodiment, by controlling the molar ratio of the phosphorus source, sodium source, fluorine source and vanadium source to 2:3:3:2, the phosphorus source, sodium source, fluorine source and vanadium source are fully reacted, thereby improving the purity of the positive electrode material; the mass ratio of the above-mentioned binder, vanadium source and complexing agent is 1:1:(1-5), which helps to improve the electrochemical performance and structural stability of the positive electrode material; a cationic modifier containing a positively charged nitrogen atom is used to undergo an etherification reaction with the hydroxyl group of reducing sugars to modify the reducing sugars, which helps to obtain a positive electrode material with improved uniformity, thereby improving the electrochemical performance of the positive electrode material; using phytic acid as a phosphorus source is beneficial to reducing costs and reducing the impact on the environment; the above-mentioned sodium source, fluorine source and vanadium source are widely available and relatively cheap, which helps to reduce process costs; the use of the above-mentioned naturally occurring complexing agent is beneficial to improving the stability and electrochemical performance of the positive electrode material while reducing the impact of the process on the environment.

[0065] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the positive electrode material described above or a positive electrode material prepared by any of the preparation methods described above.

[0066] In this embodiment, the positive electrode plate contains the above-mentioned positive electrode material, and thus has the advantages of high electronic conductivity, high sodium ion transmission efficiency, and high stability.

[0067] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate described above.

[0068] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high charging efficiency, high discharging efficiency, high energy density and long cycle life.

[0069] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0071] Figure 1 This is a flow chart of the preparation of the positive electrode material according to one embodiment of the present application.

[0072] Figure 2a~2f The diagram is a result of energy dispersive X-ray spectroscopy (EDS) of different elements of the positive electrode material of one embodiment of the present application.

[0073] Figure 3 This is a scanning electron microscope image of the positive electrode materials of Example 1, Example 2 and Example 3 of the present application, Figure 3 (a), (b) and (c) are scanning electron microscope images of the positive electrode materials of Example 1, Example 2 and Example 3 respectively.

[0074] Figure 4 This is a scanning electron microscope image of the positive electrode material of Comparative Example 1 of the present application.

[0075] Figure 5 This is a scanning electron microscope image of the positive electrode material of Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0076] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0077] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0078] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0079] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0080] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0081] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0082] In the description of the embodiments of the present application, “solution”, “reaction solution”, etc., unless otherwise specified, the solvent is water.

[0083] In the description of the embodiments of the present application, water is selected from at least one of distilled water, deionized water, pure water, and ultrapure water.

[0084] The anionic compound sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVPF) is a class of materials with potential in sodium-ion batteries. However, due to its low electronic conductivity and slow ion diffusion rate, NVPF's actual specific capacity of secondary batteries using it is low and its rate performance is not ideal, which limits its further application and development.

[0085] In order to solve the technical problems that the actual specific capacity of NVPF type positive electrode materials is low and the rate performance is not ideal when applied to secondary batteries, the present application provides a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electrical device. The positive electrode material of the present application has the following characteristics: it includes a carbon layer and sodium vanadium fluorophosphate particles distributed in the carbon layer, the carbon layer coats the sodium vanadium fluorophosphate particles, the carbon layer presents a porous network, the thickness of the carbon layer is selected from 3nm to 6nm, and the porosity of the positive electrode material is 10% to 35%. The positive electrode material of the present application effectively improves the electron transmission efficiency, increases the ion diffusion rate, and improves the wettability of the electrolyte, thereby improving the actual capacity of the positive electrode material, the positive electrode plate, the secondary battery and the electrical device, and the electrochemical properties such as cycle performance and rate performance are also improved.

[0086] In a first aspect, an embodiment of the present application provides a positive electrode material, including a carbon layer and sodium vanadium fluorophosphate particles distributed in the carbon layer, wherein the carbon layer covers the sodium vanadium fluorophosphate particles;

[0087] The carbon layer is in a porous network shape, and the thickness of the carbon layer is selected from 3nm to 6nm;

[0088] The porosity of the positive electrode material is 10% to 35%.

[0089] In some embodiments, the thickness of the carbon layer is selected from 4 nm to 6 nm, which is beneficial to better improve the electronic conductivity of the positive electrode material and enhance the thermal stability of the positive electrode material.

[0090] Optionally, the thickness of the carbon layer includes 3nm, 3.2nm, 3.5nm, 3.6nm, 3.8nm, 4nm, 4.2nm, 4.5nm, 4.6nm, 4.8nm, 5nm, 5.1nm, 5.2nm, 5.5nm, 5.6nm, 5.8nm, 6nm, etc.

[0091] In some embodiments, the porosity of the positive electrode material is selected from 13% to 33%, which is beneficial to better improve the electronic conductivity of the positive electrode material and enhance the thermal stability of the positive electrode material.

[0092] Further, the porosity of the positive electrode material can be selected from 15% to 20%, which is more conducive to taking into account both the electronic conductivity of the positive electrode material and the thermal stability of the positive electrode material. Optionally, the porosity of the positive electrode material includes 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, etc.

[0093] In the technical solution of the embodiment of the present application, the carbon layer of the positive electrode material presents a porous network, and the porous network carbon layer structure is uniformly coated with sodium vanadium fluorophosphate particles, has a suitable porosity, and the carbon layer also has a suitable thickness, which provides a more efficient channel for the transmission of electrons and improves the electronic conductivity of the material. At the same time, it is also beneficial to the penetration of electrolyte and the rapid transmission of sodium ions, further improving the charge and discharge efficiency and electrochemical performance of the corresponding secondary battery.

[0094] See also Figure 2a to Figure 2f ,and Figure 3 In some embodiments, the carbon layer structure of the positive electrode material is uniformly distributed on the surface or inside of the sodium vanadium fluorophosphate particles to form an in-situ carbon-doped structure, so that the carbon layer uniformly covers the sodium vanadium fluorophosphate particles and forms a conductive network, thereby enhancing the bonding force between the sodium vanadium fluorophosphate particles and the carbon layer. The pores are evenly distributed and have good connectivity between the pores, forming a continuous and interconnected network structure. This structure improves the conductivity of the positive electrode material and provides an efficient channel for the transmission of sodium ions, which is beneficial to the rapid diffusion and migration of sodium ions in the positive electrode material, thereby improving the rate performance of the secondary battery and enhancing the structural stability of the positive electrode material.

[0095] In some embodiments, the cathode material has at least one of the following characteristics:

[0096] (1) The pore size of the carbon layer is 2nm to 8nm.

[0097] (2) Specific surface area is 10m 2 / g~50m 2 / g.

[0098] (3) Powder resistivity ≤ 80000Ω·cm.

[0099] In some embodiments, the pore size of the carbon layer of the positive electrode material is selected from 2nm to 6nm, which is conducive to better maintaining the structural stability of the positive electrode material and providing a more efficient channel for the transmission of electrons. At the same time, it is also conducive to the penetration of the electrolyte and the rapid transmission of sodium ions. It can be understood that if the pore size is too large, it may cause the electrolyte to penetrate the carbon layer to increase, thereby forming a high-impedance interface layer, increasing the internal resistance of the secondary battery, and the excessive pore size may cause the continuity and uniformity of the carbon layer to deteriorate, destroy the transmission channel of sodium ions, and affect the diffusion efficiency of sodium ions; on the contrary, if the pore size is too small, it is not conducive to the penetration of the electrolyte, affecting the wettability of the electrolyte, and is also not conducive to the diffusion of sodium ions. Optionally, the pore size of the carbon layer includes 2nm, 2.2nm, 2.5nm, 2.6nm, 2.8nm, 3nm, 3.1nm, 3.2nm, 3.5nm, 3.6nm, 3.8nm, 4nm, 4.2nm, 4.5nm, 4.6nm, 4.8nm, 5nm, 5.2nm, 5.5nm, 5.6nm, 5.8nm, 6nm, 6.2nm, 6.5nm, 6.6nm, 6.8nm, 7nm, 7.2nm, 7.5nm, 7.6nm, 7.8nm, 8nm and the like.

[0100] In some embodiments, the specific surface area of ​​the positive electrode material is selected from 13 m 2 / g~45m 2 / g, which is conducive to better maintaining the structural stability of the positive electrode material and providing a more efficient channel for the transmission of electrons. At the same time, it is also conducive to better achieving the penetration of the electrolyte and the rapid transmission of sodium ions.

[0101] Furthermore, the specific surface area of ​​the positive electrode material can be selected from 13m 2 / g~27m 2 / g, which is more conducive to maintaining the structural stability of the positive electrode material, improving the electronic conductivity of the positive electrode material and the transmission efficiency of sodium ions, and at the same time, it is more conducive to the penetration of the electrolyte. Optionally, the specific surface area of ​​the positive electrode material includes 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, 26m 2 / g, 27m 2 / g, 28m 2 / g, 29m 2 / g, 30m 2 / g, 31m 2 / g, 32m 2 / g, 33m 2 / g, 34m 2 / g, 35m 2 / g, 36m 2 / g, 37m 2 / g, 38m 2 / g, 39m 2 / g, 40m 2 / g, 41m 2 / g, 42m 2 / g, 43m 2 / g, 44m 2 / g, 45m 2 / g, 46m 2 / g, 47m 2 / g, 48m 2 / g, 49m 2 / g, 50m 2 / g, etc.

[0102] In some embodiments, the powder resistivity of the positive electrode material of the present application is ≤80000Ω·cm, which is beneficial to improving the electronic conductivity of the positive electrode material of the present application.

[0103] In some embodiments, the powder resistivity of the positive electrode material is selected from 30000 Ω·cm to 80000 Ω·cm, which is beneficial to improve the electronic conductivity of the positive electrode material.

[0104] Furthermore, the powder resistivity of the positive electrode material can be selected from 30000Ω·cm to 50000Ω·cm, which is more conducive to improving the electronic conductivity of the positive electrode material.

[0105] Optionally, the powder resistivity of the positive electrode material includes 33000Ω·cm, 35000Ω·cm, 36000Ω·cm, 38000Ω·cm, 40000Ω·cm, 41000Ω·cm, 42000Ω·cm, 45000Ω·cm, 46000Ω·cm, 48000Ω·cm, 50000Ω·cm, 51000Ω·cm, 52000Ω·cm, 55 000Ω·cm, 56000Ω·cm, 58000Ω·cm, 60000Ω·cm, 61000Ω·cm, 62000Ω·cm, 65000Ω·cm, 66000Ω ·cm, 68000Ω·cm, 70000Ω·cm, 72000Ω·cm, 75000Ω·cm, 76000Ω·cm, 78000Ω·cm, 80000Ω·cm, etc.

[0106] In a second aspect, the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0107] S100: Mix reducing sugars and an alkaline solution to obtain a first dispersion.

[0108] S200: The first dispersion is mixed with the cationic modifier, and subjected to a first reaction treatment to obtain an adhesive.

[0109] S300: mixing a binder, a phosphorus source, a sodium source, a fluorine source, a vanadium source and a complexing agent to obtain a precursor solution.

[0110] S400: The precursor solution is treated by microwave reaction to obtain a gel slurry.

[0111] S500: After the gel slurry is dried, it is calcined to obtain a positive electrode material.

[0112] In the technical solution of the embodiment of the present application, reducing sugars are used as raw materials, and a macromolecular adhesive is formed through cationic chemical modification. Precursors and complexing agents such as phosphorus sources, sodium sources, and vanadium sources are combined, and a tight composite structure is formed after microwave-assisted hydrothermal treatment. After calcination, a positive electrode material with a suitable porous mesh carbon layer is obtained.

[0113] The carbon material itself has good conductivity, and the porous structure in the carbon layer of the positive electrode material facilitates the penetration of the electrolyte and the rapid transmission of sodium ions, thereby improving the charge and discharge efficiency and thermal stability of the corresponding secondary battery and extending the service life of the secondary battery.

[0114] In the positive electrode material, the porous carbon structure is compounded with NVPF in an in-situ co-doping manner, and the porous network carbon layer uniformly covers the sodium vanadium fluorophosphate particles to form a conductive network and is tightly combined with the sodium vanadium fluorophosphate particles, which not only ensures the continuity of ion transmission and improves the electronic conductivity of the material, but also effectively alleviates the change in the volume of the material during the charge-discharge process and enhances the structural stability of the material. The porous network of the carbon layer of the positive electrode material is also conducive to the penetration of the electrolyte and the rapid transmission of sodium ions, further improving the charging rate, discharge rate and electrochemical performance of the secondary battery.

[0115] In step S100, reducing sugars and an alkaline solution are mixed to obtain a first dispersion. This step is beneficial to activate the hydroxyl groups in the reducing sugars.

[0116] Among them, the reducing sugars can be selected from reducing sugars having glucose units such as starch, cellulose, maltose, and sucrose.

[0117] After the reducing sugar is mixed with the alkaline solution, the hydroxyl groups in the reducing sugar are ionized, so that after the subsequent mixing with the cationic modifier, the cationic modifier is connected to the reducing sugar molecules through an etherification reaction, thereby obtaining an adhesive. Exemplarily, after the reducing sugar is mixed with the alkaline solution, at a suitable temperature and for a suitable time, the reducing sugar particles absorb water and eventually break, releasing the reducing sugar molecular chains, and activating the hydroxyl groups in the reducing sugar molecules, and subsequently reacting with the cationic modifier, thereby obtaining an adhesive.

[0118] The concentration of the alkaline solution affects the activation rate of reducing sugars and the properties of the activated reducing sugars. An appropriate alkaline concentration is beneficial to promoting the gelatinization of reducing sugar particles, making the hydroxyl groups in the reducing sugars more active and easier to react with the etherifying agent.

[0119] It can be understood that if the alkali concentration is too high, a gel layer will form on the surface of the reducing sugar particles, hindering the penetration of the cationic modifier, thereby reducing the reaction efficiency and hindering the modification of the cations. If the alkali concentration is too low, the hydroxyl groups in the reducing sugars are not fully ionized, reducing the chance of reaction with the cationic modifier, resulting in an incomplete reaction. At the same time, due to the insufficient activation of the reducing sugars, the reaction efficiency is also reduced.

[0120] In some embodiments, the hydroxide ion concentration in the alkaline solution is 0.1 mol / L to 0.5 mol / L, which is beneficial to obtain a better activation effect, improve the reaction efficiency, and the degree of ionization of the hydroxyl groups in the reducing sugars is appropriate, which fully reacts with the cationic modifier, and is beneficial to obtain a binder with a suitable degree of cationic modification.

[0121] Optionally, the hydroxide ion concentration in the alkaline solution includes 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc.

[0122] In some embodiments, the step of mixing the reducing sugar and the alkaline solution to obtain a first dispersion comprises:

[0123] mixing the reducing sugar and the alkaline solution at a first mixing temperature for a first mixing time to obtain a first dispersion;

[0124] Wherein, the first mixing temperature is 40° C. to 80° C., and the first mixing time is 0.5 h to 3 h.

[0125] Optionally, the first mixing temperature includes 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., and the first mixing time includes 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, etc.

[0126] In step S200, the first dispersion is mixed with a cationic modifier and subjected to a first reaction treatment to obtain an adhesive. In this step, the cationic modifier is connected to the reducing sugar via an ether bond to obtain a reducing sugar with cationic modification, which is used as an adhesive.

[0127] Cationic modifiers usually contain positively charged nitrogen atoms and can undergo etherification reactions with the hydroxyl groups of reducing sugars, thereby connecting to reducing sugar molecules to modify them. Cationic modified reducing sugars (binders) are beneficial for improving the conductivity of positive electrode materials due to their modified groups. The binder also has improved dispersibility and reactivity, which is beneficial for providing good interfacial compatibility for its subsequent composite process and helps to form a uniform positive electrode material.

[0128] Optionally, the cationic modifier includes at least one of 2,3-epoxypropyltrimethylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride and 2-diethylaminoethylammonium chloride.

[0129] In some embodiments, the molar ratio of the cationic modifier to the glucose unit in the first dispersion is (1-4):1. Herein, the glucose unit refers to the basic structural unit constituting the polysaccharide chain, and the molecular formula is C6H 12 O6 means, for example, that the glucose unit of sucrose is 2.

[0130] Optionally, the molar ratio of the cationic modifier to the glucose unit in the first dispersion includes 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1 and the like.

[0131] In some embodiments, the step of mixing the first dispersion with the cationic modifier and subjecting the mixture to a first reaction treatment to obtain an adhesive comprises:

[0132] After the first dispersion liquid and the cationic modifier are mixed, the first reaction liquid is obtained by reacting at a first reaction temperature for a first reaction time;

[0133] The first reaction liquid is subjected to a neutralization treatment and then a purification treatment to obtain an adhesive;

[0134] Among them, the first reaction temperature is 30°C to 60°C, and the first reaction time is 6h to 10h.

[0135] Optionally, the first reaction temperature includes 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, etc., and the first reaction time includes 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, etc.

[0136] In some embodiments, the step of neutralizing the first reaction solution comprises:

[0137] Adding a pH adjuster to the first reaction solution to a pH value of 6 to 7 to obtain a pre-treated solution;

[0138] The pretreatment solution is stirred for 6 to 10 hours at a pH of 6 to 7 and 50 to 90°C to ensure a complete neutralization reaction.

[0139] In some embodiments, the pH adjuster is an acid solution, so as to adjust the pH value of the first reaction solution to 6-7. For example, the acid solution is an aqueous solution of hydrochloric acid, an aqueous solution of sulfuric acid, an aqueous solution of nitric acid, etc.

[0140] In some embodiments, the hydrogen ion concentration in the acid solution is 0.1 mol / L to 0.5 mol / L, which is conducive to more accurately adjusting the pH value of the first reaction solution.

[0141] Optionally, the hydrogen ion concentration in the acid solution includes 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc.

[0142] Optionally, in the step of neutralizing the first reaction liquid, the stirring temperature of the pretreatment liquid includes 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., and the stirring time includes 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, etc.

[0143] Before adding the pH adjuster to the first reaction liquid, an appropriate amount of water may be added to dilute the first reaction liquid to 2 to 4 times the original volume of the first reaction liquid, so as to ensure smooth subsequent pH adjustment.

[0144] Furthermore, after the first reaction liquid is neutralized, the step of purifying the first reaction liquid comprises:

[0145] The neutralized first reaction solution was dialyzed.

[0146] Furthermore, the step of dialyzing the neutralized first reaction solution comprises:

[0147] The neutralized first reaction solution is placed in a dialysis bag and then dialyzed with water for purification;

[0148] Optionally, the molecular weight cutoff of the dialysis bag is 3 kDa to 4 kDa, and exemplary molecular weight cutoffs include 3 kDa, 3.1 kDa, 3.2 kDa, 3.3 kDa, 3.4 kDa, 3.5 kDa, 3.6 kDa, 3.7 kDa, 3.8 kDa, 3.9 kDa, 4 kDa, and the like.

[0149] Optionally, the dialysis purification time may be 12 h to 14 h, for example, 12.5 h, 13 h, 13.5 h, etc. In the above dialysis purification process, the purification water may not be replaced, or may be replaced once or multiple times (eg, twice or three times, etc.).

[0150] In step S300, a binder, a phosphorus source, a sodium source, a vanadium source, a fluorine source, and a complexing agent are mixed to obtain a precursor solution. This step provides raw materials required for preparing the positive electrode material and mixes them to form a precursor solution.

[0151] Further, the step of mixing the binder, the phosphorus source, the sodium source, the vanadium source, the fluorine source, and the complexing agent to obtain a precursor solution comprises:

[0152] providing an aqueous solution of a binder;

[0153] The aqueous solution of the binder is mixed with the phosphorus source, the sodium source, the vanadium source, the fluorine source and the complexing agent, and then mixed at a second mixing temperature for a second mixing time to obtain a precursor solution.

[0154] Optionally, the second mixing temperature is 24°C to 26°C, for example, may be 25°C.

[0155] Optionally, the second mixing time is 0.5 h to 3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, etc.

[0156] Optionally, the aqueous solution of the binder, the phosphorus source, the sodium source, the vanadium source, the fluorine source, and the complexing agent are stirred to form a precursor solution.

[0157] Optionally, according to the crystal structure, the molar ratio of phosphorus in the phosphorus source, sodium in the sodium source, fluorine in the fluorine source, and vanadium in the vanadium source is 2:3:3:2. By precisely controlling the molar ratio of the phosphorus source, sodium source, fluorine source, and vanadium source to be 2:3:3:2, it is beneficial for each raw material to fully and completely react, thereby improving the purity of the positive electrode material.

[0158] Optionally, the mass ratio of the binder, the vanadium source and the complexing agent is 1:1:(1-5), which helps to form a uniform positive electrode material and improve the electrochemical performance and structural stability of the positive electrode material. For example, the mass ratio of the binder, the vanadium source and the complexing agent is 1:1:1, 1:1:2, 1:1:3, 1:1:4, 1:1:5, etc.

[0159] Optionally, the phosphorus source is selected from phytic acid. Phytic acid is a natural organic phosphorus source, which is beneficial to reduce costs and reduce environmental impact. Phytic acid can be used as a phosphorus source and a cross-linking agent in the technical solution of the present application. At the same time, reducing sugars are a natural high molecular organic carbon source, which is not only low in cost and widely available, but also has unique structure and chemical properties. The combination of the two can reduce the cost of the positive electrode material while improving the electrochemical performance of the positive electrode material.

[0160] Optionally, the sodium source includes at least one of sodium hydroxide, sodium fluoride, sodium carbonate and sodium bicarbonate.

[0161] Optionally, the fluorine source includes at least one of ammonium fluoride, polytetrafluoroethylene and sodium fluoride.

[0162] Optionally, the vanadium source includes at least one of ammonium vanadate and ammonium metavanadate.

[0163] The above-mentioned sodium source, fluorine source and vanadium source are widely available and relatively cheap, which helps to reduce the process cost.

[0164] Optionally, the complexing agent includes at least one of citric acid, oxalic acid and tannic acid.

[0165] The use of the above-mentioned naturally occurring complexing agent is beneficial to improving the stability and electrochemical performance of the positive electrode material while reducing the impact of the process on the environment.

[0166] In step S400, the precursor solution is treated by microwave reaction to obtain a gel slurry. This step adopts a method combining sol-gel technology and microwave hydrothermal technology, so that a porous network is initially formed and the sodium vanadium fluorophosphate precursor is evenly distributed in the network, providing a material basis for the subsequent preparation of a positive electrode material with a specific structure. After drying and calcining, the gel slurry is dried to obtain a positive electrode material having a porous mesh carbon layer and sodium vanadium fluorophosphate particles evenly distributed in the carbon layer. The carbon layer and the positive electrode material have the characteristics of any of the above technical solutions, thereby achieving improvements in electrical properties, etc.

[0167] In some embodiments, the step of treating the precursor solution with microwave reaction to obtain the gel slurry comprises:

[0168] subjecting the precursor solution to a first microwave power and a second reaction temperature for a second reaction time to obtain a gel slurry;

[0169] Wherein, the first microwave power is 200W-500W, the second reaction temperature is 120°C-160°C, and the second reaction time is 0.5h-2h.

[0170] Optionally, the first microwave power includes 200W, 250W, 300W, 350W, 400W, 450W, 500W, etc., the second reaction temperature includes 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, etc., and the second reaction time includes 0.5h, 1h, 1.5h, 2h, etc.

[0171] In step S500, the gel slurry is dried and then calcined to obtain a positive electrode material. The positive electrode material may be any of the positive electrode materials of the above technical solutions.

[0172] In some embodiments, after the gel slurry is dried, it is calcined to obtain the positive electrode material, comprising:

[0173] drying the gel slurry at a first drying temperature for a first drying time to obtain a gel dry powder;

[0174] Calcining the gel dry powder to obtain a positive electrode material;

[0175] The first drying temperature is 100° C. to 120° C., and the first drying time is 6 h to 12 h.

[0176] Optionally, the first drying temperature includes 100°C, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, etc., and the first drying time includes 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, etc.

[0177] In some embodiments, the step of calcining the gel dry powder to obtain the positive electrode material comprises:

[0178] In a first protective gas, the gel dry powder is calcined at a first temperature and for a first insulation time to obtain a first calcined material;

[0179] In a second protective gas, the first calcined material is calcined at a second calcination temperature for a second holding time to obtain a second calcined material;

[0180] The second calcined material is ground and sieved to obtain a positive electrode material.

[0181] The first protective gas and the second protective gas are independently selected from at least one of argon and nitrogen. The first calcination temperature is 350°C to 550°C, the first insulation time is 0.5h to 2h, the second calcination temperature is 700°C to 800°C, and the second insulation time is 1h to 3h.

[0182] Optionally, the heating rate for heating to the first calcination temperature is 3°C / min to 7°C / min, for example, 4°C / min, 5°C / min, 6°C / min, etc.; the heating rate for heating to the second calcination temperature is, for example, 4°C / min, 5°C / min, 6°C / min, etc.

[0183] Optionally, the flow rate of the first protective gas is 50 mL / min-120 mL / min, for example, 55 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, 100 mL / min, 110 mL / min, etc. The flow rate of the second protective gas is 50 mL / min-120 mL / min, for example, 55 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, 100 mL / min, 110 mL / min, etc.

[0184] Optionally, after the second calcined material is cooled to 40° C. to 60° C. (for example, 45° C., 50° C., 55° C., etc.), it is ground and sieved to obtain a positive electrode material.

[0185] In this embodiment, the first calcination and the second calcination are carried out in steps, which helps to achieve the segmented decomposition of the carbon source mixed with the precursor, avoiding its large-scale decomposition in a certain temperature range, generating more gas, and a large amount of other escape causing the material volume to expand significantly, resulting in excessive pores in the porous network carbon layer and reduced electrochemical performance; in addition, the segmented calcination allows the gas to escape more slowly, and better avoids the formation of a large number of void structures in the obtained positive electrode material first and then rapid shrinkage, resulting in problems such as too low compaction density, too high specific surface area, and deterioration of electrochemical performance.

[0186] Optionally, the first calcination temperature includes 350℃, 400℃, 450℃, 500℃, 550℃, etc., the first insulation includes 0.5h, 1h, 1.5h, 2h, etc., the second calcination temperature includes 700℃, 720℃, 750℃, 780℃, 800℃, etc., and the second insulation includes 1h, 1.5h, 2h, 2.5h, 3h, etc.

[0187] In this embodiment, the grinding and sieving processes are performed to obtain a positive electrode material having a suitable particle size, and the grinding process can be performed by a suitable grinding method known in the art, for example, by ball milling, and the ball milling instrument can be a planetary ball mill, etc. The sieving process can be performed by a suitable sieving method known in the art, for example, sieving using a sieve.

[0188] The preparation method of the present application can be used to prepare the positive electrode material of the first aspect, and the prepared positive electrode material can have the following characteristics: the positive electrode material includes a carbon layer and sodium vanadium fluorophosphate particles distributed in the carbon layer, and the carbon layer coats the sodium vanadium fluorophosphate particles; the carbon layer presents a porous network, and the thickness of the carbon layer is selected from 3nm to 6nm; the porosity of the positive electrode material is 10% to 35%.

[0189] In the technical solution of the embodiment of the present application, the carbon layer of the positive electrode material is in a porous network, and the porous structure of the carbon layer of the positive electrode material uniformly covers the sodium vanadium fluorophosphate particles. The porous network carbon layer has a suitable thickness and porosity, has good thermal stability, and provides a more efficient channel for the transmission of electrons, improves the electronic conductivity of the material, and is beneficial to the penetration of the electrolyte and the rapid transmission of sodium ions, thereby helping to improve the electrochemical performance of the secondary battery in terms of charging efficiency, discharging efficiency, etc., while improving the thermal stability of the secondary battery and extending the service life of the secondary battery.

[0190] In some embodiments, the positive electrode material prepared by the preparation method of the present application has at least one of the following characteristics:

[0191] (1) The pore diameter is 2nm to 8nm;

[0192] (2) Specific surface area is 10m 2 / g~50m 2 / g;

[0193] (3) Powder resistivity ≤ 80000Ω·cm.

[0194] In this embodiment, the pore size of the positive electrode material, that is, the pore size of the porous network structure presented by the carbon layer of the positive electrode material, the appropriate pore size and specific surface area are conducive to improving the conductivity and achieving the infiltration of the electrolyte, and will not affect the compaction density and structural stability of the positive electrode material. At the same time, the powder resistivity of the positive electrode material is within a suitable range, which can make the electron transmission rate within a suitable range, the electronic conductivity is good, the secondary battery rate performance is high, and the stability and safety are good.

[0195] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the positive electrode material described above or a positive electrode material prepared by any of the preparation methods described above.

[0196] In this embodiment, the positive electrode plate contains the above-mentioned positive electrode material, and thus has the advantages of high electron and sodium ion transmission efficiency and high stability.

[0197] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the above-mentioned positive electrode plate.

[0198] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high charge and discharge rate, high energy density and long cycle life.

[0199] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0200] 1. Preparation method

[0201] 1. Preparation of positive electrode materials

[0202] Example 1

[0203] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S1 of this embodiment is as follows:

[0204] (1) stirring 10 g of dry starch and 100 mL of a 0.2 mol / L NaOH aqueous solution at 60° C. (first mixing temperature) for 1 h (first mixing time) to obtain a first dispersion;

[0205] (2) After adding 2,3-epoxypropyltrimethylammonium chloride (cationic modifier) ​​to the first dispersion, the mixture is reacted at 60° C. (first reaction temperature) for 6 hours (first reaction time) to obtain a first reaction solution, wherein the molar ratio of the 2,3-epoxypropyltrimethylammonium chloride to the glucose unit in the first dispersion is 2:1.

[0206] After the first reaction liquid is cooled to room temperature, it is diluted with water to twice its original volume, and a 0.2 mol / L hydrochloric acid aqueous solution (pH adjuster) is added in batches for neutralization until the pH value of the first reaction liquid is 6.5 to obtain a pretreatment liquid. The pretreatment liquid is stirred at 70°C for 8 hours, and the pH value of the process is controlled to be 6-7 to complete the neutralization treatment. The neutralized first reaction liquid is placed in a dialysis bag and dialyzed and purified with water for 12 hours. The pore size of the dialysis bag is 3.5 kDa to obtain an adhesive.

[0207] (3) The binder is prepared into an aqueous solution with a mass fraction of 1% and mixed with phytic acid, NaOH, ammonium fluoride, NH4VO3 and citric acid at 25°C and stirred for 0.5h to obtain a precursor solution, wherein the molar ratio of phytic acid, NaOH, ammonium fluoride, and NH4VO3 is 2:3:3:2, and the mass ratio of the binder, NH4VO3 and citric acid is 1:1:4.

[0208] (4) The precursor solution was reacted under a microwave power of 300 W and a heating condition of 120° C. for 1 h to obtain a gel slurry.

[0209] (5) Dry the gel slurry at 100°C for 6 hours to obtain a gel dry powder; heat the gel dry powder to 400°C at a rate of 5°C / min at an argon gas flow rate of 100 mL / min, and keep it warm for 0.5 hours to obtain a first calcined material; continue to heat the first calcined material to 800°C at a rate of 5°C / min, and keep it warm for 1 hour to obtain a second calcined material; the second calcined material is cooled to 60°C, ground to 200 mesh, and then sieved to obtain the positive electrode material S1.

[0210] Example 2

[0211] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S2 of this embodiment is as follows:

[0212] (1) stirring 10 g of dry starch and 100 mL of a 0.1 mol / L NaOH aqueous solution at 80° C. (a first mixing temperature) for 3 h (a first mixing time) to obtain a first dispersion;

[0213] (2) After adding 3-chloro-2-hydroxypropyltrimethylammonium chloride (cationic modifier) ​​dropwise to the first dispersion, the mixture is reacted at 60° C. (first reaction temperature) for 10 h (first reaction time) to obtain a first reaction solution, wherein the molar ratio of the 3-chloro-2-hydroxypropyltrimethylammonium chloride to the glucose unit in the first dispersion is 1:1.

[0214] After the first reaction liquid is cooled to room temperature, it is diluted with water to twice its original volume, and a 0.1 mol / L hydrochloric acid aqueous solution (pH adjuster) is added in batches for neutralization until the pH value of the first reaction liquid is 6.0 to obtain a pretreatment liquid. The pretreatment liquid is stirred at 50°C for 10 hours, and the pH value of the process is controlled to be 6-7 to complete the neutralization treatment. The neutralized first reaction liquid is placed in a dialysis bag and dialyzed and purified with water for 14 hours. The pore size of the dialysis bag is 3.5 kDa to obtain an adhesive.

[0215] (3) The binder is prepared into an aqueous solution with a mass fraction of 2% and mixed with phytic acid, NaOH, ammonium fluoride, NH4VO3 and citric acid at 25°C and stirred for 3 hours to obtain a precursor solution, wherein the molar ratio of phytic acid, NaOH, ammonium fluoride, and NH4VO3 is 2:3:3:2, and the mass ratio of the binder, NH4VO3 and citric acid is 1:1:1.

[0216] (4) The precursor solution was reacted under a microwave power of 200 W and a heating condition of 160° C. for 2 h to obtain a gel slurry.

[0217] (5) Dry the gel slurry at 100°C for 12 hours to obtain a gel dry powder; heat the gel dry powder to 350°C at a rate of 5°C / min at an argon gas flow rate of 120 mL / min, and keep it warm for 2 hours to obtain a first calcined material; continue to heat the first calcined material to 800°C at a rate of 5°C / min, and keep it warm for 1 hour to obtain a second calcined material; the second calcined material is cooled to 50°C, ground to 200 mesh, and then sieved to obtain the positive electrode material S2.

[0218] Example 3

[0219] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S3 of this embodiment is as follows:

[0220] (1) stirring 10 g of dry starch and 100 mL of a 0.5 mol / L NaOH aqueous solution at 40° C. (a first mixing temperature) for 0.5 h (a first mixing time) to obtain a first dispersion;

[0221] (2) After adding 2-diethylaminoethylammonium chloride (cationic modifier) ​​to the first dispersion and mixing, the mixture is reacted at 30° C. (first reaction temperature) for 10 h (first reaction time) to obtain a first reaction solution, wherein the molar ratio of the 2-diethylaminoethylammonium chloride to the glucose unit in the first dispersion is 4:1.

[0222] After the first reaction liquid is cooled to room temperature, it is diluted with water to twice its original volume, and a 0.3 mol / L hydrochloric acid aqueous solution (pH adjuster) is added in batches for neutralization until the pH value of the first reaction liquid is 7.0 to obtain a pretreatment liquid. The pretreatment liquid is stirred at 90°C for 6 hours, and the pH value of the process is controlled to be 6-7 to complete the neutralization treatment. The neutralized first reaction liquid is placed in a dialysis bag and dialyzed and purified with water for 12 hours. The pore size of the dialysis bag is 3.5 kDa to obtain an adhesive.

[0223] (3) The binder is prepared into a 4% aqueous solution and mixed with phytic acid, NaOH, ammonium fluoride, NH4VO3 and citric acid at 25°C and stirred for 3 hours to obtain a precursor solution, wherein the molar ratio of phytic acid, NaOH, ammonium fluoride and NH4VO3 is 2:3:3:2, and the mass ratio of starch binder, NH4VO3 and citric acid is 1:1:5.

[0224] (4) The precursor solution was reacted under a microwave power of 500 W and a heating condition of 120° C. for 0.5 h to obtain a gel slurry.

[0225] (5) Dry the gel slurry at 120°C for 6 hours to obtain a gel dry powder; heat the gel dry powder to 550°C at a rate of 5°C / min at an argon gas flow rate of 50 mL / min, and keep it warm for 0.5 hours to obtain a first calcined material; continue to heat the first calcined material to 700°C at a rate of 5°C / min, and keep it warm for 3 hours to obtain a second calcined material; the second calcined material is cooled to 40°C, ground to 200 mesh, and then sieved to obtain the positive electrode material S3.

[0226] Example 4

[0227] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S4 of the present application is the same or similar to that of Example 1, except that in step (2), the molar ratio of the glucose unit of 2,3-epoxypropyltrimethylammonium chloride added dropwise to the first dispersion is 0.8 mol:1 mol.

[0228] Example 5

[0229] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S5 of the present application is the same or similar to that of Example 1, except that in step (2), the molar ratio of the glucose unit of 2,3-epoxypropyltrimethylammonium chloride added dropwise to the first dispersion is 5 mol:1 mol.

[0230] Example 6

[0231] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S6 of the present application is the same or similar to that of Example 1, except that in step (3), the mass ratio of starch binder, NH4VO3 and citric acid is 1:1:5.

[0232] Example 7

[0233] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S11 of the present application is the same or similar to that of Example 1, except that in step (3), the mass ratio of starch binder, NH4VO3 and citric acid is 1:1:6.

[0234] Example 8

[0235] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S12 of the present application is the same or similar to that of Example 1, except that the microwave power set in step (4) is 100W.

[0236] Example 9

[0237] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S13 of the present application is the same or similar to that of Example 1, except that the microwave power set in step (4) is 600W.

[0238] Example 10

[0239] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S14 of the present application is the same or similar to that of Example 1, except that the reaction time in step (4) is 0.2h.

[0240] Embodiment 11

[0241] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material S15 of the present application is the same or similar to that of Example 1, except that the reaction time in step (4) is 3 hours.

[0242] Example 12

[0243] An embodiment of the positive electrode material of the present application. The preparation method of the positive electrode material S16 of the present application is the same or similar to that of Example 1, except that after obtaining the gel dry powder in step (5), the gel dry powder is heated to 700°C at a rate of 5°C / min at an argon gas flow rate of 100 mL / min, and is directly kept warm for 3.5 hours without further calcination.

[0244] Example 13

[0245] An embodiment of the positive electrode material of the present application. The preparation method of the positive electrode material S17 of the present application is the same or similar to that of Example 1, except that after obtaining the gel dry powder in step (5), the gel dry powder is heated to 550°C at a rate of 5°C / min at an argon gas flow rate of 50 mL / min, and is directly kept warm for 3.5 hours without further calcination.

[0246] Embodiment 14

[0247] An embodiment of the positive electrode material of the present application. The preparation method of the positive electrode material S17 of the present application is the same or similar to that of Example 1, except that after obtaining the gel dry powder in step (5), the gel dry powder is heated to 550°C at a rate of 5°C / min at an argon gas flow rate of 50mL / min, and kept warm for 3h to obtain a first calcined material.

[0248] Embodiment 15

[0249] An embodiment of the positive electrode material of the present application. The preparation method of the positive electrode material S17 of the present application is the same or similar to that of Example 1, except that after obtaining the first calcined material in step (5), the temperature is further increased to 700°C at a rate of 5°C / min and kept warm for 0.5h to obtain the first calcined material.

[0250] Comparative Example 1

[0251] A comparative example of the positive electrode material of the present application, the difference between the preparation method of the positive electrode material D1 of this comparative example and that of Example 1 is that: in step (4), the precursor solution is subjected to hydrothermal treatment, the temperature of the hydrothermal reaction is 150°C, the time is 12h, and the pressure is 8MPa to obtain a slurry.

[0252] Comparative Example 2

[0253] A comparative example of the positive electrode material of the present application, the difference between the preparation method of the positive electrode material D2 of this comparative example and that of Example 1 is that: in step (4), the precursor solution is subjected to sol-gel treatment, comprising the following steps: the precursor solution is reacted under heating conditions of 100° C. for 24 hours to obtain a slurry.

[0254] 2. Preparation of secondary batteries

[0255] The positive electrode materials prepared in each embodiment and comparative example are prepared into positive electrode sheets corresponding to the above. The general method for preparing the above positive electrode sheets is as follows: the positive electrode material, conductive carbon black and carboxymethyl cellulose are mixed in a mass ratio of 8:1:1, and deionized water is added to make a slurry; the slurry is evenly coated on the aluminum foil with a scraper, and the coated sheet is dried at 60°C for 1h, and then rolled and cut to obtain a circular positive electrode sheet with a diameter of 12mm. The test shows that the active material loading on the positive electrode sheet is 2.8mg / cm 2 .

[0256] After drying each positive electrode sheet, assemble into a CR2035 button battery in a glove box, and place the battery in a constant temperature drying oven for 12 hours for standby use. The general method for preparing the above battery is as follows: assemble in the order of negative electrode shell, sodium sheet, electrolyte, porous polyolefin separator, NaClO4 electrolyte, positive electrode sheet, gasket, spring sheet, and positive electrode shell.

[0257] 2. Test Method

[0258] 1. Property test of positive electrode materials

[0259] (1) Porosity: Refer to TCSTM 00553-2022 Porosity determination method for lightweight porous materials.

[0260] (2) The thickness of the carbon layer and the pore size of the porous network of the carbon layer were observed using TEM.

[0261] (3) Specific surface area: tested using BET tester and nitrogen adsorption method.

[0262] (4) Powder resistivity: The test was conducted using a four-probe method at a pressure of 10 MPa.

[0263] (5) Element distribution: An energy dispersive X-ray (EDS) detector was used to perform surface distribution analysis and detect the distribution of each element. The test was conducted under the conditions of an accelerating voltage (HV) of 15 kV, a peak width (FW) of 29.3 μm, a working distance (WD) of 8.870 mm, and a pressure of 0.10 Pa.

[0264] 2. Properties test of secondary batteries

[0265] (1) Charge specific capacity: The amount of charge that can be stored per unit mass or per unit volume of an electrode material during charging.

[0266] (2) Discharge specific capacity: The amount of charge that can be released per unit mass or per unit volume of the electrode material during the discharge process.

[0267] (3) 1C cycle 100-cycle capacity retention rate: The ratio of the remaining capacity of the battery to the initial capacity after the battery has been charged and discharged for 100 cycles at a 1C rate.

[0268] (4) Rate performance test: Charge-discharge tests were performed at 0.2C, 1C, and 10C rates, with one cycle tested at each rate.

[0269] The above tests were all conducted using Wuhan Blue Power CT2001A battery testing system with a voltage range of 2.0V to 4.0V.

[0270] III. Analysis of test results of various embodiments and comparative examples

[0271] Figure 2a to Figure 2f is the distribution of each element in the positive electrode material of Example 1 of the present application, according to Figure 2a to Figure 2f It can be seen that the C element, F element, O element, P element, Na element and V element are evenly distributed in the positive electrode material. It can be seen that the sodium vanadium fluorophosphate of the positive electrode material of the present application is evenly distributed in the carbon layer, the purity of the sodium vanadium fluorophosphate is high, and there are no other impurities.

[0272] See also Figure 3 , Figure 3 (a), (b) and (c) are scanning electron microscope images of the positive electrode materials of Example 1, Example 2 and Example 3 respectively; Figure 3It can be seen intuitively that the positive electrode materials of the present application all present an obvious three-dimensional porous structure, the pore size distribution is relatively uniform, and the pores have good connectivity, forming a continuous and interconnected network structure.

[0273] See also Figure 4 , Figure 4 It is a scanning electron microscope image of comparative example 1; Figure 4 It can be seen that the positive electrode material obtained by hydrothermal treatment in Comparative Example 1 presents an obvious spherical morphology. These spherical particles are stacked together, with a diameter of approximately 100 μm to 200 μm. The spherical surface is relatively smooth with some tiny protrusions or depressions.

[0274] See also Figure 5 , Figure 5 This is the SEM image of Comparative Example 2. Figure 5 The middle right picture is an enlarged view of part of the area in the left picture; Figure 5 It can be seen that the positive electrode material obtained by the gel-sol method in Comparative Example 2 shows obvious particle stacking, a smaller pore size, and random distribution of carbon particles.

[0275] 3. Performance characterization of positive electrode materials

[0276] Table 1 shows the porosity of the positive electrode materials corresponding to Examples 1 to 15 and Comparative Examples 1 to 2.

[0277]

[0278]

[0279] Table 2 shows the charge and discharge performance of the secondary batteries corresponding to Examples 1 to 15 and Comparative Examples 1 to 2.

[0280]

[0281]

[0282] According to Table 2, the secondary battery with the positive electrode material of the present application has a good initial discharge capacity at a low rate such as 0.2C rate, and the initial discharge capacity is 112mAh / g~131mAh / g. As the rate increases, the initial discharge capacity of the secondary battery decreases slightly but does not change much, and still has a good initial discharge capacity. When the rate is increased to 10C, it can still reach 88mAh / g~103mAh / g. Compared with the secondary battery with the positive electrode material of Comparative Example 1 and the secondary battery with the positive electrode material of Comparative Example 2, the initial discharge capacity is significantly reduced at medium and high rates such as 1C rate and 10C rate, and the rate performance is significantly improved.

[0283] According to Table 2, although the secondary battery with the positive electrode material of Comparative Example 1 and the secondary battery with the positive electrode material of Comparative Example 2 have good initial discharge capacity at low rates such as 0.2C rate, the initial discharge capacity is significantly reduced at medium and high rates such as 1C rate and 10C rate, gradually decreasing from 103.6 mAh / g to 93.24 mAh / g and 77.34 mAh / g, and gradually decreasing from 102.23 mAh / g to 92.01 mAh / g and 71.81 mAh / g, respectively. It can be seen that the rate performance of the secondary battery is poor.

[0284] Table 3 shows the cycle performance of the secondary batteries corresponding to Examples 1 to 15 and Comparative Examples 1 to 2.

[0285]

[0286]

[0287] According to Table 3, the secondary battery with the positive electrode material of the present application has a high capacity retention rate after 100 cycles at a 1C rate. In some embodiments, the capacity retention rate of 100 cycles at a 1C rate can reach more than 90%, indicating that the secondary battery with the positive electrode material of the present application has a better cycle life. And the secondary battery with the positive electrode material of the present application has a high battery efficiency after 100 cycles at a 1C rate. In some embodiments, the capacity efficiency of 100 cycles at a 1C rate can reach more than 90%, indicating that the secondary battery with the positive electrode material of the present application has a high actual efficiency.

[0288] In summary, the positive electrode material provided in the present application uniformly coats the sodium vanadium fluorophosphate particles through the porous structure of the carbon layer of the positive electrode material. The appropriate thickness and porosity of the porous network carbon layer have good thermal stability while providing a more efficient channel for the transmission of electrons, thereby improving the electronic conductivity of the positive electrode material, and facilitating the penetration of the electrolyte and the rapid transmission of sodium ions, thereby effectively improving the actual capacity of the secondary battery having the positive electrode material. The secondary battery exhibits stable cycle performance and high cycle life and rate performance.

[0289] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material, characterized in that: It comprises a carbon layer and sodium vanadium fluorophosphate particles distributed in the carbon layer, wherein the carbon layer covers the sodium vanadium fluorophosphate particles; The carbon layer is in a porous network shape, and the thickness of the carbon layer is selected from 3nm to 6nm; The porosity of the positive electrode material is 10% to 35%.

2. The positive electrode material according to claim 1, characterized in that The positive electrode material has at least one of the following characteristics: (1) The pore size of the carbon layer is 2 nm to 8 nm; (2) Specific surface area is 10m 2 / g~50m 2 / g; (3) Powder resistivity ≤ 80000Ω·cm.

3. A method for preparing a positive electrode material, characterized in that: The steps include: mixing the reducing sugar and the alkaline solution to obtain a first dispersion; The first dispersion is mixed with a cationic modifier and subjected to a first reaction treatment to obtain an adhesive; The binder, a phosphorus source, a sodium source, a fluorine source, a vanadium source and a complexing agent are mixed to obtain a precursor solution; The precursor solution is treated by microwave reaction to obtain a gel slurry; The gel slurry is dried and then calcined to obtain the positive electrode material.

4. The method for preparing the positive electrode material according to claim 3, characterized in that: The step of mixing the reducing sugar and the alkaline solution to obtain a first dispersion comprises: mixing the reducing sugar and the alkaline solution at a first mixing temperature for a first mixing time to obtain the first dispersion; Wherein, the first mixing temperature is 40°C to 80°C, and the first mixing time is 0.5h to 3h; and / or, The concentration of hydroxide ions in the alkaline solution is 0.1 mol / L to 0.5 mol / L.

5. The method for preparing the positive electrode material according to claim 3, characterized in that: The step of mixing the first dispersion with the cationic modifier and subjecting the mixture to a first reaction treatment to obtain an adhesive comprises: After the first dispersion liquid and the cationic modifier are mixed, reacting at a first reaction temperature for a first reaction time to obtain a first reaction liquid; After the first reaction liquid is neutralized, it is purified to obtain the adhesive; Wherein, the first reaction temperature is 30°C to 60°C, the first reaction time is 6h to 10h; and / or, The molar ratio of the cationic modifier to the glucose unit in the first dispersion is (1-4):

1.

6. The method for preparing the positive electrode material according to claim 5, characterized in that: The step of neutralizing the first reaction liquid comprises: Adding a pH adjuster to the first reaction solution to a pH value of 6 to 7 to obtain a pre-treatment solution, Stirring the pretreatment solution at a pH value of 6 to 7 and a temperature of 50° C. to 90° C. for 6 to 10 hours; and / or, The step of purifying the first reaction solution after neutralization treatment comprises: The neutralized first reaction solution is dialyzed.

7. The method for preparing the positive electrode material according to claim 3, characterized in that: The step of treating the precursor solution with microwave reaction to obtain a gel slurry comprises: subjecting the precursor solution to a first microwave power and a second reaction temperature for a second reaction time to obtain the gel slurry; Wherein, the first microwave power is 200W-500W, the second reaction temperature is 120°C-160°C, and the second reaction time is 0.5h-2h.

8. The method for preparing the positive electrode material according to claim 3, characterized in that: The gel slurry is dried and then calcined to obtain the positive electrode material, comprising: The gel slurry is dried at a first drying temperature for a first drying time to obtain a gel dry powder, calcining the gel dry powder to obtain the positive electrode material, Wherein, the first drying temperature is 100° C. to 120° C., and the first drying time is 6 h to 12 h; and / or, The step of calcining the gel dry powder to obtain the positive electrode material comprises: In a first protective gas, the gel dry powder is calcined at a first calcination temperature for a first insulation time to obtain a first calcined material. In a second protective gas, the first calcined material is calcined at a second calcination temperature and for a second holding time to obtain a second calcined material; The second calcined material is subjected to grinding and screening to obtain the positive electrode material; Wherein, the first protective gas and the second protective gas are protective gases, the first calcination temperature is 350°C to 550°C, the first insulation time is 0.5h to 2h, the second calcination temperature is 700°C to 800°C, and the second insulation time is 1h to 3h; The protective gas includes at least one of argon and nitrogen.

9. The method for preparing the positive electrode material according to any one of claims 3 to 8, characterized in that: At least one of the following conditions is met: (1) the molar ratio of the phosphorus element in the phosphorus source, the sodium element in the sodium source, the fluorine element in the fluorine source, and the vanadium element in the vanadium source is 2:3:3:2; (2) The mass ratio of the binder, the vanadium source and the complexing agent is 1:1:(1-5); (3) The cationic modifier includes at least one of 2,3-epoxypropyltrimethylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride and 2-diethylaminoethylammonium chloride; (4) The phosphorus source includes phytic acid; (5) The sodium source comprises at least one of sodium hydroxide, sodium fluoride, sodium carbonate and sodium bicarbonate; (6) The fluorine source comprises at least one of ammonium fluoride, polytetrafluoroethylene and sodium fluoride; (7) The vanadium source includes at least one of ammonium vanadate and ammonium metavanadate; (8) The complexing agent includes at least one of citric acid, oxalic acid and tannic acid.

10. A positive electrode sheet, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 2 or the positive electrode material prepared by the preparation method according to any one of claims 3 to 9.

11. A secondary battery, characterized in that: Including the positive electrode sheet as claimed in claim 11.

Citation Information

Cited By

  • Lithium iron phosphate composite material and preparation method thereof, positive pole piece and energy storage device

    CN122291487A

  • Lithium iron phosphate composite material, preparation method thereof, positive electrode sheet and energy storage device

    CN122291487B